Aplikasi 3D Printer Fused Deposite Material (FDM) pada Pembuatan Pola Cor - Hamid Abdillah; Ulikaryani Ulikaryani (University of Muhammadiyah Jakarta, 2019)
Metal Casting Industry has a classic problem in handling the production process and quality assurance. This research aims to provide solutions to solve the problems of the metal casting industry by introducing and applying 3D printers with a fused deposit material system. this technology is used to streamline the production process of cast patterns. The process of making a casting pattern usually takes 70% of the total production time of a cast product. The purpose of this study is to examine the application of making cast patterns with a 3D printer with a fused deposit material system. The research methods carried out are (1) create of 3D CAD cast patterns, (2) conversion to STL format, (3) 3D printer setup, (4) printing process, (5) analysis, (6) conclusions. The results obtained are a 3D printer with a fused deposit material system that can be used to make cast patterns. From the analysis of the accuracy of the cast pattern with the 3D printer has a difference in size ranging from 0.2 mm. As for the analysis of the quality of the geometry, the results of the cast pattern of the 3D printer with the fused deposit material system have a good shape but lack results on the surface. Thus a 3D printer with a fused deposit material system is suitable for making cast patterns because it has a consistent tendency and ease in making cast patterns. This opens up opportunities for continued development of 3D printers in the metal casting industry sector.